How to Deal With Economic Depression: Experimental and Theoretical Lessons from the Great Depression - Ognjen Radonjić (University of Belgrade, 2016)
The purpose of this paper is to explain not only why the Euro Area debt crisis does not subside, but also, why it deepens. We believe that the experience of the Great Depression can help economic theorists and officials to look at the problem from a different perspective since it is apparent that the economic orthodoxy and economic policies supported by its conventional wisdom do not provide desired results. Roosevelt’s fiscal activism and Keynes’ revolutionary theory deliver an answer to the question of why is, in crisis periods, vigorous reaction of economic authorities needed and why the free market is not able by itself to find way out of the fog, which, as time passes, becomes more and more dense.